Extremum seeking control based on the super-twisting algorithm. Issue 2 (2020) - Torres, Ixbalank; López-Caamal, Fernando; Hernández-Escoto, Héctor; Vargas, Alejandro
Abstract: This article addresses the problem of extremum seeking of a continuous-time dynamical system with a single input and a single output. First, a super-twisting-based gradient-based optimization algorithm is proposed to compute the input that leads to the extremum value of an unknown, convex objective function. Since the algorithm requires the input-output gradient of the system's response, a super-twisting based differentiator is proposed to compute the gradient using the measured output and the controlled input. Feasibility of the extremum seeking controller is demonstrated via closed-loop simulations over a microalgae production photobioreactor.